2022
DOI: 10.1186/s12937-021-00749-7
|View full text |Cite
|
Sign up to set email alerts
|

Validation and reproducibility of a semi-qualitative food frequency questionnaire for assessment of sodium intake in Iranian population

Abstract: Background Few semi-quantitative food frequency questionnaires (SFFQ)s has yet been developed to assess sodium intake in Middle East region. This study was performed to validate a SFFQ for assessment of sodium consumption and food groups΄ contribution to sodium intake. Methods This study was performed on 219 healthy participants including 113 adults aged ≥19 years and 106 children aged 6–18 years in Isfahan, Iran. They were administered two SFFQ at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 41 publications
(46 reference statements)
3
1
0
Order By: Relevance
“…Consistency with the previous works ( 14 , 15 , 17 , 24 , 25 , 33 , 34 , 37 , 41 ), the correlation coefficient between the Sodium-FFQ and 3-day dietary records were 0.393 ( Spearman ) and 0.485 (de-attenuated), respectively. The correlation coefficients between Sodium-FFQ and 24 h U Na were lower than Sodium-FFQ with dietary records; this was in line with the existing studies (ranging from 0 to 0.37) ( 15 , 24 , 25 ).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Consistency with the previous works ( 14 , 15 , 17 , 24 , 25 , 33 , 34 , 37 , 41 ), the correlation coefficient between the Sodium-FFQ and 3-day dietary records were 0.393 ( Spearman ) and 0.485 (de-attenuated), respectively. The correlation coefficients between Sodium-FFQ and 24 h U Na were lower than Sodium-FFQ with dietary records; this was in line with the existing studies (ranging from 0 to 0.37) ( 15 , 24 , 25 ).…”
Section: Discussionsupporting
confidence: 87%
“…The current study demonstrated an acceptable reproducibility of the Sodium-FFQ, consistent with those of other studies ( 12 , 34 ). The intra-group correlation coefficient ( ICC ) also revealed a moderate association between the test and retest of 0.571, within the range of previous studies from 0.43 to 0.97 ( 33 , 34 , 37 ). The ICC varies significantly among studies might be because of the test–retest interval ( 25 ), sample size ( 10 , 24 ), dietary disparities ( 38 ), and sex and age differences of subjects ( 13 , 33 ).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The sixth shortcoming is the absence of a criterion describing the degree in which healthy lifestyle measures need to be fulfilled to allow us to say it is sufficient to change the diagnosis from "apparent treatment-resistant HTN" to the "resistant HTN". For example, how should we check patients' salt intake in everyday practice: 24-h urinary sodium excretion, food frequency questionnaire, spot urine collection, or another tool [33,[37][38][39][40]? How realistic are self-reports?…”
Section: Remarks (Insufficiencies In the Definition Of Resistant Htn)...mentioning
confidence: 99%